Preparation of PVA/PAA nanofibers containing thiol-modified silica particles by electrospinning as an eco-friendly Cu (II) adsorbent - Kim, Jinyeong; Kang, Taeho; Kim, Hyewon; Shin, Hong Ju; Oh, Seong-Geun (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Surface of silica nanoparticles was modified with thiol groups through sol–gel method.•Modified silica particles were incorporated into PVA/PAA nanofibers by eco-friendly electrospinning process.•Adsorption capacity of Cu (II) ions onto PVA/PAA nanofibers dramatically increased by incorporation of thiol-modified silica.•Adsorption behavior was rather chemisorption due to strong interaction between Cu (II) ions and thiol groups. Using an electrospinning technique, thiol-modified silica nanoparticles were incorporated into poly(vinyl alcohol) (PVA) and poly(acrylic acid) (PAA) hybrid nanofibers to fabricate an eco-friendly adsorbent with enhanced Cu (II) adsorption capacity. The hybrid nanofibers were successfully crosslinked through heat treatment. Cu (II) adsorption characteristics of nanofibers were investigated including silica quantity, surface modification, and pH. Adsorption isotherms and kinetics fit a Langmuir isotherm model and pseudo-second-order model, respectively, implying Cu (II) ion monolayer chemisorption onto the nanofibers. The resultant hybrid fibers exhibited a maximum Cu (II) adsorption capacity of 125.47 mg/g.